A Standardization Protocol for the In Situ Detection of SARS-CoV2 RNA and Proteins. Issue 2 (February 2022) - Nuovo, Gerard J.; Suster, David; Tili, Esmerina; Awad, Hamdy; Magro, Cynthia
Abstract : This manuscript details a stringent protocol for the in situ detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) RNA and 4 different viral proteins: envelope, spike, membrane, and nucleocapsid. Key aspects of the protocol are: (1) analysis of adjacent (serial) sections for viral RNA and at least 2 viral proteins; (2) cytologic alterations in the cells scored as virus positive based on an hematoxylin and eosin stain; (3) in situ demonstration of a host response in the cells scored as virus positive; (4) co-labeling experiments that show that the viral RNA and/or proteins co-localize with each other and the angiotensin converting enzyme 2 (ACE2) receptor; and (5) lack of signal in equivalent tissues obtained before the pandemic. Optimization conditions for the four viral proteins as well as the ACE2 receptor were each antigen retrieval in an EDTA solution which facilitates co-expression analyses. It is recommended not to use either electron microscopy or qRTPCR as methods to corroborate in situ SARS-CoV2 detection. This stringent protocol, that relies on sequentially labeled serial sections and can be completed in one working day, demonstrated the following: (1) infectious SARS-CoV2 is abundant in the lung in fatal coronavirus disease-2019 and is seen primarily in macrophages and endothelial cells; (2) circulating viral capsid proteins (spike, envelope, membrane without RNA) are evident in multiple organs including the skin and brain where it is endocytosed by ACE2 + cells and induce an endothelialitis; (3) both the infectious virus and circulating spike protein induce complement activation and cytologic changes in the viral positive cells.